Estimating the effect of calorie menu labeling on calories purchased in a large restaurant franchise in the southern United States: quasi-experimental study. (30th October 2019) - Petimar, Joshua; Zhang, Fang; Cleveland, Lauren P; Simon, Denise; Gortmaker, Steven L; Polacsek, Michele; Bleich, Sara N; Rimm, Eric B; Roberto, Christina A; Block, Jason P
Abstract: Objective: To evaluate whether calorie labeling of menus in large restaurant chains was associated with a change in mean calories purchased per transaction. Design: Quasi-experimental longitudinal study. Setting: Large franchise of a national fast food company with three different restaurant chains located in the southern United States (Louisiana, Texas, and Mississippi) from April 2015 until April 2018. Participants: 104 restaurants with calorie information added to in-store and drive-thru menus in April 2017 and with weekly aggregated sales data during the pre-labeling (April 2015 to April 2017) and post-labeling (April 2017 to April 2018) implementation period. Main outcome measures: Primary outcome was the overall level and trend changes in mean purchased calories per transaction after implementation of calorie labeling compared with the counterfactual (ie, assumption that the pre-intervention trend would have persisted had the intervention not occurred) using interrupted time series analyses with linear mixed models. Secondary outcomes were by item category (entrees, sides, and sugar sweetened beverages). Subgroup analyses estimated the effect of calorie labeling in stratums defined by the sociodemographic characteristics of restaurant census tracts (defined region for taking census). Results: The analytic sample comprised 14 352 restaurant weeks. Over three years and among 104 restaurants, 49 062 440 transactions took place and 242 726 953 items were purchased. After labeling implementation, a level decrease was observed of 60 calories/transaction (95% confidence interval 48 to 72; about 4%), followed by an increasing trend of 0.71 calories/transaction/week (95% confidence interval 0.51 to 0.92) independent of the baseline trend over the year after implementation. These results were generally robust to different analytic assumptions in sensitivity analyses. The level decrease and post-implementation trend change were stronger for sides than for entrees or sugar sweetened beverages. The level decrease was similar between census tracts with higher and lower median income, but the post-implementation trend in calories per transaction was higher in low income (change in calories/transaction/week 0.94, 95% confidence interval 0.67 to 1.21) than in high income census tracts (0.50, 0.19 to 0.81). Conclusions: A small decrease in mean calories purchased per transaction was observed after implementation of calorie labeling in a large franchise of fast food restaurants. This reduction diminished over one year of follow-up.